IMPROVING THE STUDENTS’ ACHIEVEMENT ON WRITING DESCRIPTIVE PARAGRAPHS THROUGH THE APPLICATION OF TEAM PAIR SOLO - Dedi Sanjaya; Sumarsih Sumarsih (Universitas Negeri Medan, 2012)
Abstract This study attempts to improve students’ achievement in writing descriptive paragraphs through the application of Team Pair Solo. This study was conducted by using classroom action research. The subject of the research was class X/A SMA Nurul Ilmi Padangsidempuan that consisted of 32 students. The research was conducted in two cycles and the first cycle consisted of four meetings and the second cycle consisted of two meetings. The instruments of collecting data were quantitative data (Writing Test) and Qualitative data (observation sheet, interview and questionnaire sheet). Based on the writing test score, students’ score kept improving in every test. In the test I the mean was 66,4375, in the test II the mean was 78,125 and the test III the mean was 87,5625. Based on observation sheet and questionnaire sheet, it was found that teaching learning process ran well. Students were active and interest in writing. The result of the research showed that TPS can improve students’ achievement in writing descriptive paragraph. Key Words: Achievement, Descriptive, Paragraph, Team Pair Solo